Offspring conceived through ART have normal thyroid function in adolescence and as young adults. Issue 7 (8th May 2022) - Wijs, L A; Doherty, D A; Keelan, J A; Panicker, V; Burton, P; Yovich, J L; Hart, R J
Abstract: STUDY QUESTION: Are there differences in thyroid function between adolescents and young adults conceived with and without ART? SUMMARY ANSWER: This study demonstrated no evidence of clinically relevant differences in thyroid function between adolescents and young adults conceived with and without ART. WHAT IS KNOWN ALREADY: Studies to date have reported an increase in subclinical hypothyroidism in offspring conceived after ART. It has been suggested that the increase in maternal estrogen (E2) after fresh embryo transfers could affect thyroid function of the offspring. Suboptimal thyroid function at a young age can cause irreversible damage to the central nervous system, which makes early detection and correct treatment essential. STUDY DESIGN, SIZE, DURATION: The Growing Up Healthy Study (GUHS) is a prospective cohort study, which aimed to recruit all adolescents born after conception with ART between 1991 and 2001 in the study area. The included participants (n = 303, aged 13–20 years) completed various health assessments. Depending on the age at enrolment, participants completed thyroid assessments at the 14- or 20-year follow-up. The outcomes of these replicated thyroid assessments were compared to those of participants conceived without ART from the Raine Study Generation 2 (Gen2). The Gen2 participants (n = 2868) were born between 1989 and 1992 and have been recognized to be representative of the local population. PARTICIPANTS/MATERIALS, SETTING, METHODS: Thyroid function assessments were compared between n = 134 GUHS and n = 1359 Gen2 adolescents at age 14 years and between n = 47 GUHS and n = 914 Gen2 young adults at age 20 years. The following mean thyroid hormone concentrations were compared between the cohorts: thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4) and thyroid peroxidase antibodies (TPOAb). The prevalence of the following thyroid hormone profiles, based on individual thyroid hormone concentrations, was compared: euthyroidism, subclinical and overt hypo- and hyperthyroidism and thyroid autoimmunity. Outcomes were compared between the cohorts, and univariately between fresh embryo transfers (ET) and frozen ET (FET) within the GUHS. The correlation between maternal peak E2 concentrations (pE2) and fT4 was assessed within the GUHS. MAIN RESULTS AND THE ROLE OF CHANCE: All mean thyroid function outcomes fell within the normal range. At both ages, we report no differences in TSH concentrations. At age 14 years, lower fT3 concentrations (4.80 versus 5.35 pmol/L, P  < 0.001) and higher fT4 concentrations (12.76 versus 12.19 pmol/L, P  < 0.001) were detected in the GUHS adolescents compared to Gen2 adolescents. At age 20 years, higher fT3 and fT4 concentrations were reported in GUHS adolescents (4.91 versus 4.63 pmol/L, P  = 0.012; 13.43 versus 12.45 pmol/L, P  < 0.001, respectively) compared to Gen2 participants. No differences in the prevalence of subclinical and overt hypo- and hyperthyroidism or thyroid autoimmunity were demonstrated between the cohorts at age 14 and 20 years. Thyroid function did not differ between ET and FET, and no correlation between pE2 and fT4 was reported. LIMITATIONS, REASONS FOR CAUTION: The observational nature of the study limits the ability to prove causation. Furthermore, the comparison of ET and FET offspring at age 20 years may be lacking power. We were unable to differentiate between different types of ART (e.g. IVF versus ICSI) owing to the low number of ICSI cycles at the time of study. As ART laboratory and clinic data were collected contemporaneously with the time of treatment, no other data pertaining to the ART cycles were sought retrospectively; hence, some factors could not be accounted for. WIDER IMPLICATIONS OF THE FINDINGS: This study does not support previous findings of clinically relevant differences in thyroid function when comparing a cohort of adolescents conceived after ART to counterparts conceived without ART. The minor differences detected in fT3 and fT4 were considered not biologically relevant. Although these findings appear reassuring, they warrant reinvestigation in adulthood. STUDY FUNDING/COMPETING INTERESTS: This project was funded by an NHMRC Grant (Hart et al., ID 1042269). R.J.H. is the Medical Director of Fertility Specialists of Western Australia and a shareholder in Western IVF. He has received educational sponsorship from MSD, Merck-Serono and Ferring Pharmaceuticals. P.B. is the Scientific Director of Concept Fertility Centre, Subiaco, Western Australia. J.L.Y. is the Medical Director and a shareholder of PIVET Medical Centre, Perth, Western Australia. TRIAL REGISTRATION NUMBER: N/A.